Short term effectiveness of methotrexate in the treatment of active Rheumatoid Arthritis - Taqweem, Amjad; Ahmed, Ibrar; Alam, Intikhab; Ali, Zafar; ., Nowsherwan; Mehboob, Amjad (Journal of Postgraduate Medical Institute, 2011)
Objective: To determine the effectiveness of six month treatment with Methotrexate in a dose range of 5-15 md once weekly in 103 patients with active Rheumatoid Arthritis